Time lost on task-, relationship and process conflict - Dirrler, Phyllis; Podruzsik, Szilárd (Business: Theory and Practice, 2023)
There are various ways to measure conflict costs, however no study has considered the distinction of conflict types in the approaches yet. The purpose of this study is to measure internal indirect conflict costs in terms of lost time and to evaluate the association to task-, relationship-, and process conflict. An online survey with 507 respondents was conducted to gather data on individual conflict situations. The measurement of internal indirect conflict costs and different conflict types was based on former research. Multiple Regression and Kruskal-Wallis testing was used to test our hypotheses. We found support that relationship conflict influences the amount of lost time on internal indirect conflict costs. Task conflict did not indicate any significant association. Process conflict demonstrated mixed results. The overall variable did not have a significant effect, however in case of international conflict set-ups process conflict was significantly linked to conflict costs. The multiple regression has an explanatory power of approximately 25%. Future research should consider other variables to be included affecting internal indirect conflict costs. Process conflict should also be researched thoroughly again. The distinction of logistical and contribution conflict was not possible.